2011
DOI: 10.3892/etm.2011.361
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of monocarboxylate transporter 4 expression in patients with colorectal cancer

Abstract: Abstract. Cancer cells generally have a high rate of glycolysis and produce larger quantities of lactate as compared to the surrounding normal cells. Monocarboxylate transporter 4 (MCT4) is one of the proton pumps exchanging the lactate through the plasma membrane. The prognostic significance of MCT4 expression has not been evaluated in patients with colorectal cancer (CRC). Surgical specimens from 105 CRC patients were immunohistochemically stained using a polyclonal anti-MCT4 antibody. The relationships amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 33 publications
3
33
1
Order By: Relevance
“…Lactate is exported from stromal cells undergoing aerobic metabolism to adjacent epithelial cancer cells, consistent with the ‘reverse Warburg effect' [37,38]. Two studies suggested that MCT4 overexpression is associated with a poor prognosis in certain cancer types [39,40]. …”
Section: Discussionmentioning
confidence: 75%
“…Lactate is exported from stromal cells undergoing aerobic metabolism to adjacent epithelial cancer cells, consistent with the ‘reverse Warburg effect' [37,38]. Two studies suggested that MCT4 overexpression is associated with a poor prognosis in certain cancer types [39,40]. …”
Section: Discussionmentioning
confidence: 75%
“…Recent studies identified the monocarboxylate transporter 4 (MCT4) as metabolic target in a variety of tumors (e.g., colon cancer, breast cancer; refs. 7,8). MCT4 (encoded by the SLC16A3 gene) mediates the H þ -coupled transport of monocarboxylates, preferentially lactate, across the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…In tumor cells, several studies have indicated that the invasion behavior of MCT4 positive cancer cells is stronger than cells not expressing MCT4 (Izumi et al, 2011). It is also proposed that high tumor cells MCT4 expression predicted poor outcomes in several cancers (Pertega-Gomes et al, 2011;Meijer et al, 2012;Nakayama et al, 2012). However, tumors are composed of both tumor and stromal cells, and the latter can comprise over 50% of the tumor mass.…”
Section: Discussionmentioning
confidence: 99%
“…A number of original studies that investigating clinical and prognostic significances of MCT4 and CA IX level have been conducted in various types of cancers (Chen et al, 2005;Pinheiro et al, 2010;Rademakers et al, 2011;Nakayama et al, 2012;Kim et al, 2014). Nevertheless, clinical values of stromal MCT4 and CA IX in GC remain not entirely clear.…”
Section: Introductionmentioning
confidence: 99%